2012
DOI: 10.5923/j.fph.20120201.11
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment of Wheat Biscuits and Fortified Wheat Biscuits with Citrus Peels Powders

Abstract: Citrus peels, the waste by-products of citrus juices factories are reckoned valuable healthful functional food.The present investigation performed to assess nutritional status of wheat and fortified biscuits with citrus peels powders. Study included determination of gross chemical composition, caloric value , minerals (Fe, Mn, Cu, Ca, Mg, Na, K and P) of wheat and fortified biscuits with citrus peels powders. Likewise physical and sensory characteristics of control and 10% fortified wheat biscuits with the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
4
9
1
Order By: Relevance
“…Moreover, the aggregation of SFPC induced formation of protein network, which helped increase the elasticity and extensibility of the dough, thus leading to increased spread ratio. The findings of this study is in harmony with earlier work reported [23,49]. This assertion is also confirmed by sensory data in Figure 2.…”
Section: Biscuit Physical Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the aggregation of SFPC induced formation of protein network, which helped increase the elasticity and extensibility of the dough, thus leading to increased spread ratio. The findings of this study is in harmony with earlier work reported [23,49]. This assertion is also confirmed by sensory data in Figure 2.…”
Section: Biscuit Physical Analysissupporting
confidence: 93%
“…Eneche [54] reported 5.0 to 6.6% moisture content of biscuit and recommended that these values are better for shelf life stability of biscuits. Moisture content obtained in this study was slightly lower than moisture content (5.30-7.50%) reported by Youssef and Mousa [49] and slightly higher than moisture content (3.56-4.26%) reported by [1]. This might be attributed due to difference in raw materials, fish species and processing techniques used in the study.…”
Section: Parameterscontrasting
confidence: 73%
“…This may probably due to the high content of orange and apple peels compared to pomegranate peels. Similar increase was observed by Youssef and Mousa [35]. after incorporation of 10% orange peels to biscuits.…”
Section: Nutritional Composition Of Biscuits Supplemented With Fruit Peelingssupporting
confidence: 85%
“…Beetroot (Beta vulgaris L.) is a root vegetable, recognized as health-promoting food due to the presence of essential components such as vitamins, minerals, phenolics, carotenoids, nitrates, and betalains. Beetroot has been used in different products like yoghurt (Yadav, Masih, & Sonkar, 2016), probiotic drink (Panghal, Virkar et al, 2017), ice cream (Manoharan, Ramasamy, Kumar, Dhanalashmi, & Balakrishnan, 2012), jelly (Chaudhari & Nikam, 2015), candy (Fatma, Sharma, Singh, Jha, & Kumar, 2016), multigrain snacks (Dhadage, Shinde, & Gadhave, 2014), and cookies (Amnah, 2013;Youssef & Mousa, 2012). Beetroot is a boon to the food industry because it is predominantly used as food colorant or food additive in various food products.…”
Section: Introductionmentioning
confidence: 99%
“…Beetroot is a boon to the food industry because it is predominantly used as food colorant or food additive in various food products. Beetroot has been used in different products like yoghurt (Yadav, Masih, & Sonkar, 2016), probiotic drink (Panghal, Virkar et al, 2017), ice cream (Manoharan, Ramasamy, Kumar, Dhanalashmi, & Balakrishnan, 2012), jelly (Chaudhari & Nikam, 2015), candy (Fatma, Sharma, Singh, Jha, & Kumar, 2016), multigrain snacks (Dhadage, Shinde, & Gadhave, 2014), and cookies (Amnah, 2013;Youssef & Mousa, 2012). Beetroot has been added in the form of juice, pomace powder, and dried root powder in noodles and extrudates by various researchers (Kim et al, 2015;Shim, Kim, & Bae, 2003;Sinha & Masih, 2014).…”
Section: Introductionmentioning
confidence: 99%